Swimming intensity during triathlon: A review of current research and strategies to enhance race performance - Peeling, P.; Landers, G. (Journal of Sports Sciences, 2009)
The swim section of Sprint- and Olympic-distance triathlon race formats is integral to the success of subsequent cycle and running disciplines, and to overall race performance. The current body of swimming-based triathlon research suggests that the energy used, and the positioning gained among competitors during the swim, is important in determining the success of an athlete's race, especially professional athletes in draft-legal settings. Furthermore, by swimming at a reduced intensity, it has been shown that the performance of the subsequent disciplines may be enhanced. However, reductions in energy output can be obtained without compromising swimming speed. This review highlights the importance of swimming intensity during a triathlon and how it impacts on the ensuing cycle and run. Furthermore, consideration is given to current methods used to manipulate swimming performance.